Análise nutriconal de mudas de Apuleia leiocarpa (Vogel) J. F. Macbr. em diferentes doses de N, P e K - Oliveira, Gisele Gomez de (2013)
Apuleia leiocarpa (grápia) is a native forest species with wide distribution in Brazil as well as in neighboring countries such as Argentina, Bolivia, Paraguay, Peru and Uruguay, inhabiting preferentially hillsides. The wood is considered valuable and is obtained from extractive way, and in view of the interest, it is in danger of extinction and is classified as vulnerable. Faced with this, studies are needed to subsidize the cultivation of grapia plants. This study aimed to determine whether there is interaction between the combined rates of N, P and K, as well as establishing nutritional parameters for seedlings Apuleia leiocarpa (Vogel) J. F. Macbr., From the application of different doses of nutrients, using soil Red Argissoil aluminic abruptc. The seedlings were grown in pots polypropylene capacity of 2.5 dm3 of soil with different doses of nutrients. Treatments were obtained by combining the N levels (50, 100, and 150 mg dm-3), P (150, 300, and 450 mg dm-3) and K (50, 100, and 150 mg dm-3) plus an control treatment which was not added nutrients, resulting in unbalanced factorial experiment arranged in a completely randomized design (CRD) with 6 replicates resulting in 168 sampling units. The variables morphological height (H), stem diameter (DC), height/stem diameter (H/DC), shoot dry matter (SDM), root dry weight (RDW) and total dry matter (MST), and the variables leaf area, root length and nutrient content in the leaves. The seedlings were maintained for 120 days in a greenhouse with monitoring of temperature and relative humidity. The combination of different doses of N, P and K showed that there was a differential response in the growth of seedlings Apuleia leiocarpa in Red Argisoil aluminic abruptic. N levels interfere with the content of nutrients in the leaf. Doses above 100 mg dm-3 of N interfere negatively on seedling growth of young plants. The use of 450 and 150 mg dm-3 of P and K, respectively, is recommended to fertilize grápia plants in Red Argisoil aluminic abruptic. Additional studies with intermediate doses of 50 and 100 mg dm-3 of N should be performed.